The Studio and the Craftsman as Artist: A Study in Periodical Poetics (1893–1900) - Catherine Delyfer (Cahiers Victoriens et Edouardiens)
The unprecedented boom in the art periodical press of the late nineteenth century contributed to shape and redefine the role of the artist in the eyes of the public. This paper examines the visual and discursive constructions and reconfigurations of the persona of the decorative artist in the influential fin de siècle magazine for the fine and applied arts The Studio. Founded in 1893 by Charles Holme and edited by Gleeson White, this periodical was created to proclaim the achievements of the Arts and Crafts designers. As any periodical, however, The Studio was a commercial venture too. Both a financial and an artistic success, it managed skillfully to combine serious articles by expert critics, popular New Journalism features, and beautiful illustrations. Analyzing the successive magazine covers, the visual matrix of the magazine, the rubric dedicated to artists’ interviews and the “Lay Figure” editorial pages, this study examines the poetics of the magazine to show how this periodical successfully promoted the craftsman (traditionally viewed as a practitioner of low arts) as the ideal liberal artist (high art). In The Studio, the craftsman became the new artistic paradigm, thus leading to major changes in the readers’ perception of the artist, the nature of art and their relation to industry and commerce.